The ultimatum [large type] - Robards, Karen (Wheeler Publishing, a part of Gale, Cengage Learning, 2017)
Thief. Manipulator. Con artist. Bianca St. Ives is the best in the business. Her father prepped her well to carry on the family business. She's known as the Guardian. Running a multinational firm with her father, she makes a living swindling con men out of money they stole-- and she does things on her own terms. But her latest gig had two hundred million dollars and top secret government documents going missing. Her father also died on the mission. The thing is, the US government doesn't believe he's really dead... and they mean to use Bianca as bait.